EFEK PROPOLIS SEBAGAI RENOPROTEKTOR TERHADAP GAMBARAN HISTOPATOLOGI GINJAL MENCIT YANG DIINDUKSI PARASETAMOL - Baihaqi, Achmad Alfan; AD, Noor Yazid; Marfu’ati, Nanik (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
The use of paracetamol with a toxic dose of 15 grams/day can cause damage, one of which is the kidney in the form of acute tubular necrosis. Propolis has a renoprotector effect through an antioxidant mechanism. The purpose of this study is to identify the renoprotector effect of propolis on the histopathological appearance of paracetamol-induced mouse kidneys. This research was an experimental research using the Post Test Only Control Group Design method. The sample of this study were 28 Swiss Webster mice divided into 4 groups: group (K-) was not given propolis and paracetamol, group (K+) was given paracetamol at a dose of 250 mg/kg BW; group (P1) was given propolis at a dose of 0.100 ml and group (P2) 0.125 ml was then induced by paracetamol at a dose of 250 mg/kgBW. The research was conducted for 10 days. Data were analyzed using the One Way Anova and Post Hoc LSD tests to determine whether there were significant differences in the histopathological appearance of the kidneys between treatment groups. The One Way Anova test showed significant differences in all treatment groups with p<0.05. The results of the LSD Post Hoc test showed that there was a significant difference between the K- group and the K + group, between the K + group and the P1 and P2 groups there was a significant difference. There was no significant difference between group P1 and group P2. There was an effect of propolis renoprotector on the histopathological appearance of paracetamol-induced mouse kidneys. Giving propolis at a dose of 0.100 ml was more optimal in preventing kidney damage in mice than a dose of 0.125 ml.